7(7x+-3y)-y-4=0

Simple and best practice solution for 7(7x+-3y)-y-4=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(7x+-3y)-y-4=0 equation:


Simplifying
7(7x + -3y) + -1y + -4 = 0
(7x * 7 + -3y * 7) + -1y + -4 = 0
(49x + -21y) + -1y + -4 = 0

Reorder the terms:
-4 + 49x + -21y + -1y = 0

Combine like terms: -21y + -1y = -22y
-4 + 49x + -22y = 0

Solving
-4 + 49x + -22y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 49x + 4 + -22y = 0 + 4

Reorder the terms:
-4 + 4 + 49x + -22y = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 49x + -22y = 0 + 4
49x + -22y = 0 + 4

Combine like terms: 0 + 4 = 4
49x + -22y = 4

Add '22y' to each side of the equation.
49x + -22y + 22y = 4 + 22y

Combine like terms: -22y + 22y = 0
49x + 0 = 4 + 22y
49x = 4 + 22y

Divide each side by '49'.
x = 0.08163265306 + 0.4489795918y

Simplifying
x = 0.08163265306 + 0.4489795918y

See similar equations:

| (3m+1)(2m-2)= | | -3/8=3/4 | | x^3-2400=0 | | -3n+2(2+2n)=-1 | | 5-c=22 | | 12=-11b+4 | | 4(x^2+100)=0 | | -3n+2(2+2n)=1 | | 5(4c-1)-4=16c+7 | | 4n+2n-3=27 | | 2n+14=-8 | | 11x+8(-x-10)=9 | | y=.25x+9 | | 25+5y-8=16y-10-2y | | 6+8+x=9+5 | | -15x+5x=30x | | -1.6=-0.5u+0.1u | | 24=7+x | | -1.6=-0.5+0.1u | | 23=2v-17 | | 5x+11=-74-7x | | 5x+45=2x+18 | | 2a+9b-9a-3b= | | 7-31=-4z | | 74-6=7x+22 | | 2p(3-3p)= | | 8x^2-69x+40=0 | | 2p(3-3o)= | | f(x)=4x^2+16x+45 | | f(x)=4x^2+16+45 | | 8+15y= | | -4x+1=25 |

Equations solver categories